Base-Mediated Synthesis of 2-Bromobenzoheterocycles - Arora, Ramon; Li, Shangyu; Stommer, Maik; Mirabi, Bijan; Lautens, Mark (Synthesis, 2024)
A base-mediated cyclization to synthesize 2-bromobenzoheterocycles is reported. This transformation was demonstrated with 16 examples to access a broad range of brominated benzoheterocycles. Mechanistic studies support the reaction proceeds through a bromoalkyne, and revealed an exchangeable proton at C3 of the indole products.
Keywords: heterocycles; transition-metal-free; chromatography-free; base-mediated cyclization